2016
DOI: 10.1055/s-0036-1571348
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bezafibrate on the Survival of Random Skin Flaps in Rats

Abstract: Background Bezafibrate is widely used in clinics for its comparable angiogenic effect. Our research is to investigate the effect of bezafibrate on random skin flap survival. Materials and Methods The "McFarlane flap" rat models were established in 30 male Sprague-Dawley rats which were divided into two groups. The treatment group was given bezafibrate (400 mg/kg/day; gavage administration), and the control group received the vehicle. The flap surviving area was measured after 7 days, and the tissue samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…For instance, Cheng et al, Lin et al, and Kailiang et al investigated protective effects of tirofiban (a widely used antiplatelet medication), bezafibrate, and muscone (one of the most well-known Chinese traditional medicines) in the McFarlane random-pattern skin flap model, respectively. [39][40][41] In the first study, the authors found that tirofiban could improve the SFS probably through angiogenic activities by increasing the expression of vascular endothelial growth factor (VEGF). However, they did not investigate pharmacologic pathways in their study and administered tirofiban daily for 7 days after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Cheng et al, Lin et al, and Kailiang et al investigated protective effects of tirofiban (a widely used antiplatelet medication), bezafibrate, and muscone (one of the most well-known Chinese traditional medicines) in the McFarlane random-pattern skin flap model, respectively. [39][40][41] In the first study, the authors found that tirofiban could improve the SFS probably through angiogenic activities by increasing the expression of vascular endothelial growth factor (VEGF). However, they did not investigate pharmacologic pathways in their study and administered tirofiban daily for 7 days after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…They also administered bezafibrate for 7 consecutive days following the surgery by gavage. 40 Keiliang et al also administered muscone for 7 days after the surgery to examine the flap survival rate. In the CBD of 1 mg/kg group, more stained cells (brown cells pointed with arrows) were observed compared with the control group, showing higher capillary densities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surviving area of each flap was observed macroscopically during the injection and the appearance, tissue elasticity and hair condition were assessed. After 7 days, we measured the surviving area and total area of each flap using transparent cellophane and the weights of the flap using an electronic scale; the surviving area was calculated as a percentage [ 8 ]. The following formula was used to quantify the results: extent of the viable area × 100/the total area (viable and ischemic) [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Many agents have been reported to improve flap survival by inhibiting inflammation, increasing free-radical scavenging, promoting angiogenesis, and/or expanding the microvascular network. Such materials include VEGF [ 6 ], sildenafil [ 7 ], bezafibrate [ 8 ], aspirin [ 9 ], and some traditional Chinese medicines [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%